The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjopen-2017-021177
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Health of the Nation Outcome Scales (HoNOS) family of measures: protocol for a systematic review

Abstract: IntroductionThe Health of the Nation Outcome Scales (HoNOS) for adults, and equivalent measures for children and adolescents and older people, are widely used in clinical practice and research contexts to measure mental health and functional outcomes. Additional HoNOS measures have been developed for special populations and applications. Stakeholders require synthesised information about the measurement properties of these measures to assess whether they are fit for use with intended service settings and popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The analysis included only subjects with complete CGI and HoNOS data sets at baseline and discharge; HoNOS with three or more missing items were considered incomplete (Harris et al, 2018; James et al, 2018). To avoid an overlap of the time frame of evaluation, for the analysis of change, we excluded patients discharged the first week after admission.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis included only subjects with complete CGI and HoNOS data sets at baseline and discharge; HoNOS with three or more missing items were considered incomplete (Harris et al, 2018; James et al, 2018). To avoid an overlap of the time frame of evaluation, for the analysis of change, we excluded patients discharged the first week after admission.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it has become a well-established measurement instrument and is primarily used to assess the outcome of psychiatric treatment (Delaffon et al, 2018; James et al, 2018). In the meantime, it is available in several languages (Delaffon et al, 2018; Harris et al, 2018), and in some countries, the HoNOS is a mandatory outcome measure (Delaffon et al, 2018; Speak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies of the IRR of HONOS item ratings report a range of coefficients from very low (−0.05, Luo et al , 2016) to very good (0.88, Brooks, 2000); all report some weak item IRRs (Orrell et al , 1999; Trauer et al , 1999; Brooks, 2000; Webster et al , 2013; Luo et al , 2016). Two reviews of studies of IRR found reports of mixtures of weak and good coefficients (Jacobs, 2009; Harris et al , 2017). Item 8 (other mental and behavioural problems) may add to variability in the interpretation of items because it is used to rate a variety of difficulties; in heterogeneous samples, its “meaning” may change from rating one service user to another.…”
Section: Introductionmentioning
confidence: 99%